An Analysis Of D Band Schottky DIODE For Millimeter Wave Application - Jamil, Nur Hazirah; Ali, Nadhirah; Othman, Mohd Azlishah; Abd Aziz, Mohamad Zoinol Abidin; Sulaiman, Hamzah Asyrani (Asian Research Publishing Network (ARPN), 2015)
A Schottky Diode for millimeter wave application proposed in this paper. The proposed model includes the n-well thickness as a variable to explain the operational behavior of a planar Schottky Barrier Diode which is firstly introduced in this paper. This paper shows the differentiation the length of the n-well thickness with three lengths which are 1.6 μm, 1.4μm and 1.2μm. Then, the size of the Schottky Diode becomes too small with dimension 2.0μm x 2.0μm. The suitable materials that used in this diode are silicon where it has a more advantages than other materials. The Schottky Diode was designed by using the Silvaco TCAD tools software whereas it’s also produced the IV and CV Characteristics graph. The both of graph was be analyzes after the three comparison the length of the n-well thickness was specified the values.